Problems and prospects of classroom management among secondary school teachers in Pakistan - Zoha Muhammad Zakir; Muraina Kamilu Olanrewaju (International Journal on Education Insight, 2025)
Classroom management is a multifaceted process involving the establishment of rules, management of student behavior, and facilitation of active participation. In Pakistan, secondary school teachers encounter unique challenges that complicate these efforts. This study investigates the problems and prospects of classroom management among secondary school teachers in Sindh, Pakistan. The study adopts qualitative approach using secondary data to analyse the questions in the study. Challenges like student misbehavior, overcrowded classrooms, and resource shortages hinder effective management, while opportunities such as professional development and technology integration offer solutions. The study examines how these factors and teacher experience influence management effectiveness, guided by Choice Theory’s emphasis on student choice and relationships. The paper provides strategies to enhance teaching practices, benefiting teachers, administrators, and policymakers. It was suggested the need for the launch of community-based initiatives, such as parent-teacher meetings and awareness campaigns to increase parental involvement, reinforcing discipline and fostering a shared commitment to education among others.